Language and Art in Senegal: The Crossbreeding of Identities in Music - Sarr, Ibrahima (Advances in Social Sciences Research Journal, 2021)
Senegal is a melting pot of several civilizations mainly originated from the West (Europe) and the East (the Arab world). Assuming that language and culture are intrinsically related, the settlement of those people and their status as dominant minority sparked and strengthened the use of their languages in formal domains. In the long ran, as they became domesticated, thus now considered African languages because they have contributed to mold the cultural identity of younger generation, they involve in all linguistic interaction. Arab, in its classical form, remains a symbol of Islam which earns it a certain degree of sacredness. Nevertheless the contact situation with the other languages forced it to crossbreed in special ways like borrowings and interferences. As for the other foreign languages, namely French, English, Spanish, and German at a least extent, they are made to carry the weight of local cultures.